O psicólogo escolar na rede municipal das regiões sul e sudoeste de Goiás : concepções teóricas, práticas e desafios - Naves, Renata Magalhães (2015)
Between 2007 and 2010, an interinstitutional research was developed in seven Brazilian states, aiming to track the Scholar Psychology Services in Education Secretaries and outline the profiles of the psychologists and their modalities of services, identifying the conceptions that supported their practices and in which way they showed synchrony with recent discussions in the area. As in that occasion the State of Goiás did not take part of the study, we decided to use the same methodologic procedures, questionnaires and interviews, to investigate two regions of this state: South and Southwest. In these regions, we found 18 psychologists acting in Education Secretaries of 12 from 50 municipalities researched. The investigation, quantitative and qualitative, initially involved the application of a questionnaire, in which we raised information about the psychologist as a professional: role, graduation, target audience, modalities of services and theoretical foundation, among other aspects. The analysis of questionnaires, made with help from Excel, revealed the existence of some indicatives of performance of the psychologists on a critical perspective in Scholar Psychology. We found that, from the 16 participants, seven act based on a clinical model, seven showed evidences of a speech characterized by critical and non-critical elements and two evidenced elements of a critical speech. On the next step, interviews were made with the two psychologists, who showed a critical view, aiming deepen the answers, inquiring target audience, modalities and projects of acting and theoretical foundation. We determined the effort of the professionals in implanting actions that are not focused on the clinical pattern of performing, once that both are implementing and structuring the services in Scholar Psychology in their municipalities, something we consider a signal that advances are happening under Scholar Psychology in the studied region. Their strategies of acting cover managers, coordinators and teachers from schools, explanations about the new conceptions in Scholar Psychology and work proposals with all the evolved in the educational context (parents, students, teachers, managers), from showed school complaints. The research allowed us to observe that the related practices move in a continuum, which goes since traditional actions, in an intervention focused on the student, until consistent actions in critical Scholar Psychology. The investigation of the psychologists work who act in public education of the researched municipalities help us to think over the initial formation of these professionals as to the continuous formation they get hold of. We highlight the importance role of university in such process, in the sense of providing the theoretical-practical elements to an intervention in a reality based on depth, critic and ethic and political commitment with the Brazilian population and with their own profession. The deficient insertion of psychologists in the educational scenery of the cities and regions researched can be connected to the absence of a legislation that regulates their presence in the sphere of public school.